Primary renal sarcoma in a female patient: case report - Somang Lee; Binnari Kim (Journal of Pathology and Translational Medicine)
BCOR-rearranged sarcoma was classified by the World Health Organization in 2020 as a new subgroup of undifferentiated small round-cell sarcoma. It is known to occur very rarely in the kidney. This report presents the first case of a primary renal BCOR::CCNB3 sarcoma in a 22-year-old woman. An 8-cm cystic mass was identified in the left kidney by abdominal pelvic computed tomography. Histopathologic examination revealed the mass to be composed of small round to oval or spindle cells with fibrous septa and a delicate vascular network. A BCOR::CCNB3 fusion was detected by next-generation sequencing–based molecular testing. BCOR::CCNB3 sarcoma presents diagnostic difficulties, highlighting the importance of recognizing its histological features. Immunohistochemical markers are helpful for diagnosis, but genetic molecular testing is necessary for accurate diagnosis. These tumors have a very poor and aggressive prognosis, and an optimal therapeutic regimen has not yet been defined. Therefore, further studies are needed.